1944
DOI: 10.1104/pp.19.2.350
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Light Intensity and Rate of Photosynthesis of Loblolly Pine and Certain Hardwoods

Abstract: Onie of the most important forestry problems in the south concernis the tendency of pine stands to be succeeded by hardwoods. This occurs because pine seedlings usually fail to survive under forest canopies while the seedlings of many hardwood species survive and grow. It is often supposed that the failure of pine seedlings to grow under a forest canopy results from their high light requirements. Pine seedliings are assumed to be unable to carry on photosynthesis rapidly enough in the shade of a forest canopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
0
2

Year Published

1944
1944
1990
1990

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(59 citation statements)
references
References 7 publications
(3 reference statements)
9
48
0
2
Order By: Relevance
“…This graph is intended to show only the general relationship between root growth and light intensity. The relationship is the same as that found between photosynthesis and light intensity by KRAMER and DECKER (16). There is a rapid rise in the rate of root growth with increased light intensity at low intensities but the increase in growth rate per unit change in light intensity becomes less as the light increase,s at high intensities.…”
Section: Temperature and Leaf-root Ratiosupporting
confidence: 68%
“…This graph is intended to show only the general relationship between root growth and light intensity. The relationship is the same as that found between photosynthesis and light intensity by KRAMER and DECKER (16). There is a rapid rise in the rate of root growth with increased light intensity at low intensities but the increase in growth rate per unit change in light intensity becomes less as the light increase,s at high intensities.…”
Section: Temperature and Leaf-root Ratiosupporting
confidence: 68%
“…The supply of moisture is at least as favorable for the growth of trees at Durham as within the natural range of red pine, for the ratio of precipitation to evaporation is higher in North Carolina than in Connecticut during the summer. The maximum photoperiod in Connecticut is about forty minutes greater than that at Durham, but it seems unlikely that the photoperiod is an important factor, for it has been shown that the length of the growing season and the rate of growth of red pine at Durham were not modified by artificially prolonging the photoperiod (9). GUSTAFSON (4) reported that red pine seedlings must be subjected to freezing during the winter if they are to resume growth in the spring.…”
Section: Feet (7)mentioning
confidence: 99%
“…GUSTAFSON (4) reported that red pine seedlings must be subjected to freezing during the winter if they are to resume growth in the spring. Winters are always cold enough at Durham to insure adequate exposure to low temperature for breaking dormancy and careful observations have shown (9) that red pine resumes growth promptly in the spring. There is a consistent difference in temperature between the two regions, the mean summer temperature in Durham being higher by more than five degrees Centigrade.…”
Section: Feet (7)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the experiments have included northern red oak (Bordeau 1954 andDecker 1944). Bordeau (1954) conducted a series of experiments that demonstrated the shade tolerance of northern red oak and the shade intolerance of blackjack oak seedlings.…”
Section: Light Intensitymentioning
confidence: 99%